The Role of "Robotic Assisted Intensivist” As Solution Of Resources Management In Covid-19 Pandemic Era - Anna Surgean Veterini; Bambang Pujo Semedi; Cita Rosita Sigit Prakoeswa; Damayanti Tinduh (Indonesian Journal of Anesthesiology and Reanimation, 2021)
Providing expertise in the care of critically ill patients is one of the main needs of critical care medicine, especially in the COVID-19 pandemic era. This goal is particularly challenging, given the acknowledged shortage of intensive care specialists. We need the bedside nurse to have real-time access to get continuous reporting monitoring. The intensivist also has access to bed site examination at some time when they are not possible for coming to the intensive care unit (ICU). The big problems during COVID-19 are the limited personal protective equipment, the limited number of intensivist doctors, and the nature of the disease was very contagious and deadly. It is necessary to find a solution so as not to cause new problems, namely the death of medical staff and nurses due to frequent contact with Covid-19 patients. In this article, the author wants to open a view to getting solutions to problems in the field by presenting human replacement technology.